Building Mathematical Identity Through Gamified Learning: A Development Study Using Wordwall Platform in Junior High School - Lina Rihatul Hima (Universitas PGRI Yogyakarta, 2026)
This research aims to build students’ mathematical identity by developing gamification-based learning media on the Wordwall platform. Employing a Research and Development (R&D) approach with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), the study involved 30 seventh-grade students of SMP Negeri 4 Pare, Kediri Regency. Data were collected through observation, interviews, questionnaires, and pre–post mathematical identity tests. Expert validation results showed the media was highly valid (average score = 4.36). At the same time, the N-Gain value of 0.57 (moderate) indicated a significant improvement in students’ mathematical identity, particularly in engagement (0.66), value and meaning (0.54), and self-confidence (0.52). These findings demonstrate that gamification does not merely enhance cognitive learning outcomes but also constructs mathematical identity through positive social–emotional experiences, such as collaboration, reflection, and recognition. Theoretically, this research supports Boaler’s (2021) concept of mathematical freedom and Martin’s (2019) theory of social positioning, and, practically, offers an inclusive digital learning model that encourages confidence, engagement, and meaningful participation in mathematics. Keywords: identity mathematical, gamification, wordwall, media learning digital, ADDIE